The Degree of Leadership Practices among the Chairs of Academic Departments at Taibah University from the Perspective of Faculty Members according to the Kozes and Posner Leadership Scale - Graida, Dalal Mohammed; Alhazmi , Fatemah Abdullah (Dirasat: Educational Sciences, 2020)
This study identifies the degree of utilization of specific leadership practices by the chairs of the academic departments at Taibah University, using the Kouzes & Posner scale. The findings are based on the views of faculty members at the university. To achieve the study objectives, the researchers used a descriptive approach. Thus, the research instrument was a questionnaire comprising of 30 points divided into five dimensions based on the Kouzes & Posner scale. The study sample was a random selection of (315) faculty members. After collecting and analyzing the data, the results profile revealed moderate use of the examined leadership practices among the chairs of the academic departments. The results also showed statistically significant differences at the level of (α = 0.05) when evaluating the sample according to gender. No statistically significant differences were found due to experience, academic post held, or college.